2000
DOI: 10.1677/joe.0.1650693
|View full text |Cite
|
Sign up to set email alerts
|

The oestrogenic effects of gestodene, a potent contraceptive progestin, are mediated by its A-ring reduced metabolites

Abstract: Gestodene (17 -ethynyl-13 -ethyl-17 -hydroxy-4,15-gonadien-3-one) is the most potent synthetic progestin currently available and it is widely used as a fertility regulating agent in a number of contraceptive formulations because of its high effectiveness, safety and acceptability. The observation that contraceptive synthetic progestins exert hormone-like effects other than their progestational activities, prompted us to investigate whether gestodene (GSD) administration may induce oestrogenic effects, even th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
17
0
4

Year Published

2006
2006
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 41 publications
3
17
0
4
Order By: Relevance
“…(Maggiolini et al 1999, García-Becerra et al 2002. These data are similar, though non-identical, with our previous observations with the tetrahydro-reduced metabolites of synthetic 19-nor progestins, which are also able to transactivate oestrogen-dependent genes mediated through hERa, but not through hERb, behaving as selective hER modulators (Lemus et al 2000, Larrea et al Figure 8 Oestrogen-like transactivation effects of androstanediols. Increasing concentrations of 3a,5a-androstanediol (3a,5a-diol), 3b,5a-androstanediol (3b,5a-diol) and oestradiol (E 2 ) were incubated with HeLa cells transiently co-transfected with expression vectors for hERa or hERb and an ERE-E1b-CAT reporter gene, for 24 h, at 37 8C.…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…(Maggiolini et al 1999, García-Becerra et al 2002. These data are similar, though non-identical, with our previous observations with the tetrahydro-reduced metabolites of synthetic 19-nor progestins, which are also able to transactivate oestrogen-dependent genes mediated through hERa, but not through hERb, behaving as selective hER modulators (Lemus et al 2000, Larrea et al Figure 8 Oestrogen-like transactivation effects of androstanediols. Increasing concentrations of 3a,5a-androstanediol (3a,5a-diol), 3b,5a-androstanediol (3b,5a-diol) and oestradiol (E 2 ) were incubated with HeLa cells transiently co-transfected with expression vectors for hERa or hERb and an ERE-E1b-CAT reporter gene, for 24 h, at 37 8C.…”
Section: Discussionsupporting
confidence: 86%
“…Further interest for the conduction of this study stemmed from the recent observations in our laboratory (Lemus et al 2000, Larrea et al 2001, García-Becerra et al 2002, demonstrating that the A-ring tetrahydro-reduced metabolites of norethisterone, levonorgestrel and gestodene, possess oestrogen-agonistic activities, suggesting that they could be involved in the activation of breast cancer cell proliferation induced by high doses of synthetic contraceptive progestins derived from 19-nor testosterone, as it has been previously reported (Catherino et al 1993, Schoonen et al 1995a,1995b. …”
mentioning
confidence: 81%
See 1 more Smart Citation
“…Competition studies Stereospecificity of the binding of NET, 5a-NET, 3a,5a-NET, and 3b,5a-NET to ER, was assessed by competition analysis (Lemus et al 2000), using dexamethasone as control. Cytosol aliquots (400 mg protein/ml) were incubated with 0 .…”
Section: Binding Assays Equilibrium Parameters Of the Reaction Between [mentioning
confidence: 99%
“…Previous studies from our laboratory have demonstrated that synthetic 19-nor progestins are extensively metabolized in target organs to A-ring reduced tetrahydro derivatives (Larrea et al 1987, Lemus et al 1992), which exert estrogen-like effects (Vilchis et al 1986, Moralí et al 1990, Lemus et al 2000.…”
Section: Introductionmentioning
confidence: 99%